Strategic Management / Competitiveness and Globalization Concepts - Hitt Michael A; Hoskisson Robert E; Ireland Duane R (West Publishing Company, 1995)
Preface, Strategic Management Inputs, Strategic Management and Strategic Competitiveness, The External Environment: Opportunities and Treats and Industry Competition and Competitor Analysis, The Internal Environment: Resources and Capabilities and Core Competencies, Business-Level Strategy, Competitive Dynamics, Corporate-Level Strategy, Acquisition and Restructuring Strategies, International Strategy, Corporate Governance, Structure and Control, Strategic Leadership, Corporate Entepreneurship and Innovation, Preparing an Effective Case Analysis, Name and Company and Subject Index.
Preface, Strategic Management Inputs, Strategic Management and Strategic Competitiveness, The External Environment: Opportunities and Treats and Industry Competition and Competitor Analysis, The Internal Environment: Resources and Capabilities and Core Competencies, Business-Level Strategy, Competitive Dynamics, Corporate-Level Strategy, Acquisition and Restructuring Strategies, International Strategy, Corporate Governance, Structure and Control, Strategic Leadership, Corporate Entepreneurship and Innovation, Preparing an Effective Case Analysis, Name and Company and Subject Index.